Cell Autonomous Neuroprotection by the Mitochondrial Uncoupling Protein 2 in a Mouse Model of Glaucoma - Hass, Daniel T.; Barnstable, Colin J. (Frontiers in Neuroscience, 2019)
Glaucoma is a group of disorders associated with retinal ganglion cell (RGC) degeneration and death. There is a clear contribution of mitochondrial dysfunction and oxidative stress toward glaucomatous RGC death. Mitochondrial uncoupling protein 2 (Ucp2) is a well-known regulator of oxidative stress that increases cell survival in acute models of oxidative damage. The impact of Ucp2 on cell survival during sub-acute and chronic neurodegenerative conditions however is not yet clear. Herein, we test the hypothesis that increased Ucp2 expression will improve retinal ganglion cell survival in a mouse model of glaucoma. We show that increasing retinal ganglion cell but not glial Ucp2 expression in transgenic animals decreases glaucomatous RGC death, but also that the PPAR-γ agonist rosiglitazone, an endogenous transcriptional activator of Ucp2, does not significantly alter RGC loss during glaucoma. Together, these data support a model whereby increased Ucp2 expression mediates neuroprotection during a long-term oxidative stressor, but that transcriptional activation alone is insufficient to elicit a neuroprotective effect, motivating further research in to the post-transcriptional regulation of Ucp2.